Total Gaseous Mercury Concentration Measurements at Fort McMurray, Alberta, Canada - Matthew T. Parsons (Atmosphere, 2013)
Observations are described from total gaseous mercury (TGM) concentrations measured at the Wood Buffalo Environmental Association (WBEA) Fort McMurray—Patricia McInnes air quality monitoring station—from 21 October 2010 through 31 May 2013, inclusively. Fort McMurray is approximately 380 km north-northeast of Edmonton, Alberta, and approximately 30 km south of major Canadian oil sands developments. The average TGM concentration over the period of this study was 1.45 ± 0.18 ng∙m−3. Principal component analysis suggests that observed TGM concentrations are correlated with meteorological conditions including temperature, relative humidity, and solar radiation, and also ozone concentration. There is no significant correlation between ambient concentrations of TGM and anthropogenic pollutants, such as nitrogen oxides (NOX) and sulphur dioxide (SO2). Principal component analysis also shows that the highest TGM concentrations observed are a result of forest fire smoke near the monitoring station. Back trajectory analysis highlights the importance of long-range transport, indicating that unseasonably high TGM concentrations are generally associated with air from the southeast and west, while unseasonably low TGM concentrations are a result of arctic air moving over the monitoring station. In general, TGM concentration appears to be driven by diel and seasonal trends superimposed over a combination of long-range transport and regional surface-air flux of gaseous mercury.